The impact of transformational leadership on the effectiveness of decision-making: An applied study on General Hospital - Al-Barakani, Yousef Dwaihi (Journal of Economic, Administrative and Legal Sciences, 2024)
The study aimed to identify the impact of transformational leadership on the effectiveness of decision-making, an applied study on the general hospital. The problem of the study was to measure the impact of transformational leadership dimensions on the effectiveness of decision-making in the general hospital. The importance of the study is due to the fact that this study may add to scientific research centers, libraries, relevant institutions and those interested in this field a scientific addition that illustrates the importance of transformational leadership in decision-making in the health sector in the Kingdom of Saudi Arabia. This study may also help highlight the importance of transformational leadership in decision-making, as the extent to which the leader’s transformational leadership exists and the nature of the impact of this leadership on the decision-making process are measured, and highlights the importance of having a transformational leader who works to spread an organizational culture that is dominated by positive feelings and emotions that improve the performance of the organization, which reflects positively on the decision-making process in the organization. The hypotheses of the study were that there is a statistically significant effect at the level of significance (0.05 ≥ α) of transformational leadership on the effectiveness of decision-making in the general hospital. There are statistically significant differences at the level of significance (0.05 ≥ α) between the average scores of the study sample members on transformational leadership and decision-making effectiveness in the general hospital attributed to (gender, age, educational qualification, years of experience). To achieve the objective of the study, the researcher used the descriptive approach, and the study tool was a questionnaire that was applied to a sample consisting of (152) individual workers in the general hospital, Among the most prominent results of the study: There is an impact of the dimensions of transformational leadership (ideal effect, inspirational motivation, individual considerations, and intellectual arousal) on the effectiveness of decision-making in the hospital.